A flood management strategy for the Harvey River - Yusman, Ana Susanti (Curtin University, 2009)
This thesis is about how to managing flood and identify the appropriate flood management strategy for the Harvey River area. It is not only an analysis of the current flood management role at the Harvey River, but also how to choose the most appropriate flood management strategy in the Harvey catchment. The current research has identified major parameter that need to be consider for Harvey catchment flood strategy. Mike 11 and statistical methods were use to establish the relationship between flood height and discharge at Harvey catchment. It is recommend that before any flood management option can be made; the nature of the flood hazard must be modelled for Harvey catchment and flood maps are produced. The research recommends a combination approach to establish a strategy for Harvey catchment. This includes source control, providing storage, change in land use, flood proofing and emergency planning.